Endovascular treatment of unruptured wide-necked intracranial aneurysms: comparison of dual microcatheter technique and stent-assisted coil embolization. (25th March 2014) - Starke, Robert M; Durst, Christopher R; Evans, Avery; Ding, Dale; Raper, Daniel M S; Jensen, Mary E; Crowley, Richard W; Liu, Kenneth C
Abstract : Background: Endovascular treatment of wide-necked aneurysms is challenging. Stent-assisted coiling (SAC) is associated with increased complications and requires dual antiplatelet therapy. Objective: To compare treatment of unruptured, wide-necked aneurysms with a dual-microcatheter technique (DMT) versus SAC. Methods: Between 2006 and 2011, 100 patients with unruptured wide-necked intracranial aneurysms were treated with DMT and 160 with SAC. Over time there was a significant decrease in the use of SAC and a corresponding increase in DMT. The investigators matched 60 patients treated with DMT blinded to outcome in a 1:2 fashion based on maximal aneurysm dome diameter with 120 patients treated with SAC. Outcomes were determined with conditional (matched) multivariate analysis. Results: There were no significant differences in patient or aneurysm characteristics between cohorts, including aneurysm diameter, neck width, or volume. Overall packing density and coil volume achieved was not significantly different between cohorts. There were higher rates of overall complications in those receiving SAC (19.2%) compared with DMT (5.0%; p=0.012), but no significant difference in major complications (8.3% vs 1.7%, respectively; p=0.103). At a mean follow-up of 27.0±18.9 months, rates of retreatment did not differ between DMT (15.1%) and SAC (17.7%). Delayed in-stent stenosis occurred in five patients and in-stent thrombosis in four patients treated with SAC. There was no difference in favorable functional outcome (modified Rankin score 0–2) between those treated with DMT (90.6%) compared with SAC (91.2%). Conclusions: DMT and SAC are effective endovascular approaches for unruptured, wide-necked aneurysms; however, DMT may result in less morbidity. Further long-term studies are necessary to determine the optimal indications for these treatment options.